Analisis Faktor yang Berhubungan dengan Rencana Keluarga di Pesisir Pantai Kota Padang dalam Menghadapi Bencana - Rika Fatmadona; Rika Sabri (NERS Jurnal Keperawatan, 2014)
Padang city as the capital of West Sumatra province, is geographically laid on west coast of Sumatra island, so inevitable from disaster / ring of fire. The study was purposed to investigate factors related to family plan in the coastal of Padang city on facing the disaster. The study design was cross sectional study. Population study were involved the community in 4 districts coastal of Padang city; Lubuk Begalung District, Bungus Teluk Kabung District, Koto Tangah district, North of Padang District, and Koto Tangah District, numbering 71.046 people with quota sampling 100 people. The data was collected using a questionnaire and focus group discussions. Results indicated that families who live along the coast disasters most often experienced is the earthquake-tsunami (100%).Family’s plan in facing disaster has been good (76%), most of respondents have education level on high school(42%), respondents 42% majority work in private sector jobs, more than half of respondents (67%) have less knowledge about disaster , more than half of respondents have positive attitudes toward disaster (59%), more than half of respondents (68%) had a positive perception on disaster. From the chi square test showed a significant relationship exists between knowledge and attitudes with family plan to face disaster with p <0.05. But there is no relationship between perception, employment, disaster information with plan for disasters, where p> 0.05. The conclusion is knowledge and attitude of families living in coastal area of Padang city is closely linked to disaster response plan. But the perception, jobs and disaster information is found not closely associated with the face of disaster plans. Recommendation addressed to the local government to provide knowledge and dissemination of disaster management, quick and responsive to overcome the negative issues related to disaster risk outstanding changed public perception of the disaster.